Interferon: purification and initial characterization from human diploid cells. - Knight, E (1976)
Interferon produced by human diploid fibroblast cells in culture has been purified approximately 5000-fold. The purified interferon, when analyzed by electrophoresis on polyacrylamide gel containing sodium dodecyl sulfate, contains only one polypeptide component of 20,000 molecular weight. The interferon activity comigrates with this polypeptide, indicating identity of the activity and the polypeptide. Oxidation of this polypeptide with periodic acid and subsequent staining with Fuchsin base indicates that it contains carbohydrate ans suggests that the human fibroblast interferon is a glycoprotein.